Learning English Language through Self Development in a Technological Universities - Abdurahmanova Zulfiya Abdullayevna; Sodiqov Hamidulla Sayfulla o’g’li (International Journal on Integrated Education, 2022)
Learning English language through self-development is the most important direction for modernization of an educational system. A creative activity gives wide opportunities for developing one’s own individuality. The process of learning a foreign language contributes to forming a creative independence. Creative thinking is the highest form of activity and independent activity of a person and society. The scope of creativity includes actions from a non-standard solution to a simple problem to the full realization of an individual's unique potential in a given area.